'Macro-finance determinants and the stock market development: evidence from Morocco'. Issue 1 (2nd January 2021) - Belcaid, Karim; El Ghini, Ahmed
ABSTRACT: This paper focuses on the role of the macroeconomic outlook in explaining the returns volatility from 1998 to 2018 in Morocco. Our findings show that the inclusion of low-frequency macroeconomic information can improve the explaining ability, particularly for the long-term variance component. Information in some indicators which represent forward-looking variables (i.e. international economic situation, interest rates, exchange rates and inflation) seem to take into account the current economic situation, and remain useful in the Moroccan stock market development. Nevertheless, the historical realized volatility exceeds all models with macro-finance data in terms of explaining the long-term volatility. Therefore, it is noteworthy that investors and decision makers are considered to be more affected by the stock results, namely the past returns performance and the historical volatility. In general, modeling the long-term volatility component has a great potential and is very useful for portfolio selection, hedging decisions and macroeconomic risk management.